2014
DOI: 10.1039/c4nr02100b
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative synchrotron X-ray fluorescence study of the penetration of transferrin-conjugated gold nanoparticles inside model tumour tissues

Abstract: The next generation of therapeutic nanoparticles in the treatment of cancer incorporate specific targeting. There is implicit importance in understanding penetration of targeted nanomedicines within tumour tissues via accurate and quantitative temporospatial measurements. In this study we demonstrate the potential of state-of-the-art synchrotron X-ray fluorescence microscopy (XFM) to provide such insights. To this end, quantitative mapping of the distribution of transferrin-conjugated gold nanoparticles inside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…Transferrin is widely used for the surface modification of NPs and for tumor targeting 46,47. The cells express transferrin receptors that interact with transferrin of the delivery system.…”
Section: Introductionmentioning
confidence: 99%
“…Transferrin is widely used for the surface modification of NPs and for tumor targeting 46,47. The cells express transferrin receptors that interact with transferrin of the delivery system.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers have found that some specific molecules used as targeting agents, such as carbohydrate, 10 folic acid, 11,12 transferrin, 13,14 and some peptides, 15,16 could be modified onto the surface of NPs and achieve active targeting therapy with high specificity, selectivity, and affinity through coupling targeting molecules with their specific receptor expressed on the cell surface.…”
Section: Introductionmentioning
confidence: 99%
“…A AuNP solution (0.6 nM) was prepared by the standard sodium citrate reduction method proposed by EnĂŒstĂŒn and Turkevich (1963) and widely published in the literature (Liu et al, 2014(Liu et al, , 2015Cruje and Chithrani, 2015). AuNPs were first treated with a polyethylene glycol (PEG) solution consisting of a mix of short-chain (458.6 Da) to long-chain (2000 Da) PEG (Rapp Polymere, TĂŒbingen, Germany) at a volume ratio of 4:1 based on a previously established protocol (Liu and Thierry, 2012).…”
Section: B Aunp Preparation and Irradiation Conditionsmentioning
confidence: 99%
“…Inorganic NP content can be obtained in bulk assays with the most commonly used technique being inductively coupled plasma mass spectrometry (ICP-MS) (Subiel et al ., 2016). Laser ablation ICP-MS (Drescher et al ., 2012) and reflectance confocal microscopy are methods that have been applied to quantifying inorganic NP content at the single-cell level; however, these methods typically only provides qualitative measures of NP content (Liu et al ., 2014). Recent advances in synchrotron X-ray fluorescence (XRF) detector technology have now made it possible for statistically significant numbers of cells to be analysed for elemental content in within manageable time frames (Vogt and Lanzirotti, 2013; Kempson et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%